2018
DOI: 10.1002/hyp.13295
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in stable isotope compositions of waters from a Himalayan river: Estimation of glacier melt contribution

Abstract: Stable isotopic compositions (δ18O and δD) in water samples collected from Parbati River in Himachal Pradesh, India, during 2002–2005 were measured to delineate the contributions from different sources in different seasons. A seasonal cycle with high δ18O and δD values (in ‰) during the spring (March to May; −9.2, −58.6), intermediate values during the winter (December to February; −10.1, −65.6), and low values during the south‐west monsoon (July to September; −10.9, −71.8) is observed. The d‐excess values (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 68 publications
(165 reference statements)
0
15
0
Order By: Relevance
“…More importantly, however, recent high‐resolution δ 18 O measurements of monsoonal precipitation at multiple stations across India clearly suggest that, contrary to normal belief, there is a negligible contribution of the amount effect in Indian monsoonal rain (Eastoe and Dettman, ; Midhun et al ., ). If so, the only plausible source(s) of depleted water can be the extra‐peninsular rivers and their tributaries of the Himalayan region where glacial meltwater can contribute to generate a river water δ 18 O of −12‰ (Lone et al ., ; Laskar et al ., ). Therefore, we propose that the highly negative δ 18 O values required to explain the Dholavira T. palustris record were due to inputs from such rivers to the Gulf water of the mangrove hosting the gastropods.…”
Section: Resultsmentioning
confidence: 97%
“…More importantly, however, recent high‐resolution δ 18 O measurements of monsoonal precipitation at multiple stations across India clearly suggest that, contrary to normal belief, there is a negligible contribution of the amount effect in Indian monsoonal rain (Eastoe and Dettman, ; Midhun et al ., ). If so, the only plausible source(s) of depleted water can be the extra‐peninsular rivers and their tributaries of the Himalayan region where glacial meltwater can contribute to generate a river water δ 18 O of −12‰ (Lone et al ., ; Laskar et al ., ). Therefore, we propose that the highly negative δ 18 O values required to explain the Dholavira T. palustris record were due to inputs from such rivers to the Gulf water of the mangrove hosting the gastropods.…”
Section: Resultsmentioning
confidence: 97%
“…A previous study based on stable water isotopes shows that the WDs contribute the maximum (>70%) to the total annual precipitation in the Kashmir valley (western Himalayas), which is more than the Indian Summer Monsoon (ISM) (<30%) [15]. In contrast, a study in the Parbati Basin, western Himalayas, shows that WDs contribute a maximum up to 30% to the annual precipitation [17]. These reports clearly indicate large spatial variability in annual precipitation over the western Himalayas, particularly during the WDs.…”
Section: Introductionmentioning
confidence: 93%
“…On the contrary, another study based on a stable isotopes study suggests that the snow/glacier melt contribution to the Beas River, Western Himalaya, is up to~50% [12]. A similar study in the Parbati River, a major tributary of the Beas River, has reported that glacier melt contributes up tõ 44% (±15%) [17]. A model-based water balance approach for other Himalayan rivers like the Sutlej, Ganga and the Chenab, estimates the annual snow and glacier melt contributions up to~60% (at Bhakra Dam),~28% (at Devpryag), and~49% (at Akhnoor), respectively [26,27].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations